Preparation and Properties Study of Cr on FeCrAl Cladding Materials - Wang, Peng; Qiao, Yingjie; Qi, Wen; Du, Shiyu; Liu, Zhen; Meng, Fanping; Zhang, Xiaohong; Wang, Kun; Li, Qiuwu; Yao, Zhaoding; Bai, Chengying; Wang, XiaoDong (Frontiers in Materials, 2021)
FeCrAl alloy is a promising candidate material for the fourth-generation reactor core cladding material. Adjustment of the Cr content is one of the effective ways to obtain enhanced performance for the FeCrAl alloy. In this work, Fe-xCr-6Al alloy(11≤x≤15) with different Cr content were successfully prepared by hot rolling. When Cr replacement of Fe atoms in Fe-xCr-6Al alloy rises from 11 wt.% to 15 wt.%, the lattice distortion of Fe-xCr-6Al alloy increases, and the mechanical properties and thermal conductivity of the Fe-xCr-6Al alloy are raised. Compared with Al content, Cr content has less effect on Fe-xCr-6Al oxidation resistance.